The identification of potent nonopioid analgesics and their potential for perioperative use - Chaoyi Deng; Yu Deng; Xudong Luo; Junyu Lu; Chenyang Li; Peiwen Gao; Xiaoyu Xie; Bingbing Xiang; Sicheng Liu; Xingxing Liu; Xiaoxiao Li; Pan Chang; et al. (Proceedings of the National Academy of Sciences, 2026)
Development of potent nonopioid analgesics (NOAs) has attracted great attentions from both academic and industrial worlds, aiming at replacing current opioid drugs in acute and chronic pain management. Among the diverse proposed pathways toward nonopioid analgesia, voltage-gated sodium channel stood out as one of the most promising targets in developing potent NOA. Diverging from the prevailing focus on highly subtype-selective blockers, we report here the access of potent analgesia via the simultaneous inhibition on multianalgesic-related sodium channel subtypes. Originated from AI-driven drug discovery and computer-aided drug design, the hit and lead compounds exhibited efficient inhibitory effect on analgesic-related sodium channel subtypes, robust analgesic effect in various rat models and no opioid-related adverse reactions. Furthermore, the potential of such a multi-subtype sodium channel blocker for perioperative use was validated through a surgical simulation. These findings represent a meaningful leap toward the goal of replacing opioids in perioperative period and provide fresh insights for future NOA development.